Assessment of the performance of low-cost GNSS receivers for deformation monitoring application - Xue, Chenyu (2022)
Current deformation monitoring applications adopting GNSS technology are usually conducted with high-grade GNSS sensors, consisting of both geodetic receiver and geodetic antenna. However, the high-cost feature of the equipment constrains its broader application. With the development of state-of-art low-cost GNSS receivers/antennas in recent years, especially those with multi-GNSS precise carrier phase measurement, the potential for its application in deformation monitoring is expected. However, compared to conventionally adopted survey-grade equipment, most low-cost receivers have the major drawback of single-frequency and larger background noise in the signal processing phase, and the patch antennas have the major disadvantage of the less gain, less multipath suppression, etc. Despite the comparatively poorer quality, empirical research has demonstrated its feasibility in landslide monitoring within centimetre level of accuracy. To test the feasibility and accuracy of the low-cost equipment in other deformation applications, a systematic approach is adopted by carrying out several experiments. Experiments are conducted sequentially from zero-baseline test for internal receiver noise evaluation, short baseline static test to identify and mitigate the practical GNSS monitoring errors majorly consisted of multipath, short baseline dynamic test to determine the precision of low-cost equipment in dynamic monitoring scenario, and finally, the low-cost equipment is tested on a real bridge monitoring project to assess its feasibility and evaluate its accuracy. It is concluded that the modal frequencies from deformation monitoring could be revealed from measurements of a single low-cost rover, and with proper multipath mitigation technique, displacement amplitude could be obtained within centimetre accuracy by a closely-spaced dual low-cost system. The difference of low-cost rover measurement is quantified to be within around 3mm compared to geodetic GNSS sensors. This finding is quite promising for low-cost GNSS deformation monitoring applications. However, future investigation still needs to be carried out with a calibrated patch antenna or with a geodetic antenna to examine further improvement and possibly explore the potential of applying it in real-time.